THE IMPACT OF MONETARY INFLATION ON INVESTMENT IN EUROPEAN MARKETS - Mohammed Mahmood Thamer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Monetary policy relies on the accomplishment of a range of macroeconomic indicators such as development, efficiency and job objectives. However, monetary policy interventions, such as shifts in the central bank’s pace, at best have explicit consequences and substantial holes in the application of policy mechanisms are concerned. Fresh information such as stock, securities and bond markets, mortgage and foreign exchange markets are increasingly consumed by broader finance markets. As a result, financial data should be used to establish a simpler and more immediate effect of monetary policy changes. It is necessary to take into account the relationship between money policies and the prices of financial assets in order to get a clearer insight into the communication mechanism of monetary policy, since the variations in asset price play a major part in many networks. We include analytical information in this article regarding the relationship between monetary policy and the stock market, one of the principal capital markets. The stock levels are one of the largest tracked economic asset prices and are generally known to be highly sensitive to economic factors. Monetary behaviour affects financial markets, which are related to the real economy in the context of a bond delivery mechanism by their effects on demand and investment expenditure.